Corporate power and social policy in a global economy : British welfare under the influence - Farnsworth, Kevin (Book collections on Project MUSE., 2004)
This groundbreaking book investigates and documents corporate influence on social policies at global/regional, national and local levels. It argues that we cannot understand the recent history and present direction of the welfare state unless we focus on the role that business has played in its development.